Pembelajaran Microcontroller MCS-51 Dengan Metodologi Interaktif - Tamaji; Arief Budijanto (Jurnal Intake : Jurnal Penelitian Ilmu Teknik dan Terapan, 2017)
Evaluation Board Microcontroller 89S51 / 89S82 / 89S53 (PEM-51) is a tool used to support microcontroller subject learning with an interactive methodology. PEM-51 consists of input / output modules that are integrated in one PCB board. The modules consist of a switch input, keypad module, LED module, seven segment display module, LCD display module, ADC (Analog to Digital Converter) module, DAC (Digital to Analog Conver) module, Stepper motor module. The software used in this tool is C using the Keil µVision4 compiler. The interactive learning process can be done by making a simulation circuit using Proteus software before implementing it to a microcontroller. With PEM-51, it is expected to increase student competency in studying Microcontroller courses.